2023
DOI: 10.3390/ijms241713642
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biomaterial Surface Properties on Engineering Neural Tissue for Spinal Cord Regeneration

Victor A. da Silva,
Bianca C. Bobotis,
Felipe F. Correia
et al.

Abstract: Tissue engineering for spinal cord injury (SCI) remains a complex and challenging task. Biomaterial scaffolds have been suggested as a potential solution for supporting cell survival and differentiation at the injury site. However, different biomaterials display multiple properties that significantly impact neural tissue at a cellular level. Here, we evaluated the behavior of different cell lines seeded on chitosan (CHI), poly (ε-caprolactone) (PCL), and poly (L-lactic acid) (PLLA) scaffolds. We demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
0
1
0
Order By: Relevance
“…16 Increasing evidences indicated that the neural differentiation of ESCs could be promoted by nanomaterials with stable physicochemical properties in recent years. 12,17,18 mESCs could be effectively differentiated into neural precursors, neurons, astrocytes, and oligodendrocytes supported by nanofibrous poly(lactic-co-glycolic acid) (PLGA) 3D scaffolds, and the fraction of NPCs on PLGA aligned nanofibers was significantly higher than that of PLGA random nanofibers. 19 Encapsulating the neural differentiation factor RA in a mesoporous silica nanoparticle (MSN) significantly facilitated the neural differentiation of mESCs.…”
Section: Introductionmentioning
confidence: 99%
“…16 Increasing evidences indicated that the neural differentiation of ESCs could be promoted by nanomaterials with stable physicochemical properties in recent years. 12,17,18 mESCs could be effectively differentiated into neural precursors, neurons, astrocytes, and oligodendrocytes supported by nanofibrous poly(lactic-co-glycolic acid) (PLGA) 3D scaffolds, and the fraction of NPCs on PLGA aligned nanofibers was significantly higher than that of PLGA random nanofibers. 19 Encapsulating the neural differentiation factor RA in a mesoporous silica nanoparticle (MSN) significantly facilitated the neural differentiation of mESCs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, strong efforts have been expended in recent years toward the development of new and effective strategies for the treatment of neurological disorders and neurological trauma. However, one particular and difficult challenge neurological treatments face is the limited capacity of neuron cells to proliferate while reestablishing synaptic connections [1,2].…”
Section: Introductionmentioning
confidence: 99%